Low intraoperative end-tidal carbon dioxide levels are associated with improved recurrence-free survival after elective colorectal cancer surgery - Dehne, Sarah; Kirschner, Lina; Strowitzki, Moritz; Kilian, Samuel; Kummer, Laura; Schneider, Martin; Michalski, Christoph; Büchler, Markus W.; Weigand, Markus A.; Larmann, Jan (Journal of clinical anesthesia, 2024)
Study objective - Higher levels of carbon dioxide (CO2) increase the invasive abilities of colon cancer cells in vitro. Studies assessing target values for end-tidal CO2 concentrations (EtCO2) to improve surgical outcome after colorectal cancer surgery are lacking. Therefore, we evaluated whether intraoperative EtCO2 was associated with differences in recurrence-free survival after elective colorectal cancer (CRC) surgery. - Design - Single center, retrospective analysis. - Setting - Anesthesia records, surgical databases and hospital information system of a tertiary university hospital. - Patients - We analyzed 528 patients undergoing elective resection of colorectal cancer at Heidelberg University Hospital between 2009 and 2018. - Interventions - None. - Measurements - Intraoperative mean EtCO2 values were calculated. The study cohort was equally stratified into low-and high-EtCO2 groups. The primary endpoint measure was recurrence-free survival until last known follow-up. Groups were compared using Kaplan-Meier analysis. Cox-regression analysis was used to control for covariates. Sepsis, reoperations, surgical site infections and cardiovascular events during hospital stay, and overall survival were secondary outcomes. - Main results - Mean EtCO2 was 33.8 mmHg ±1.2 in the low- EtCO2 group vs. 37.3 mmHg ±1.6 in the high-EtCO2 group. Median follow-up was 3.8 (Q1-Q3, 2.5-5.1) years. Recurrence-free survival was higher in the low-EtCO2 group (log-rank-test: p = .024). After correction for confounding factors, lower EtCO2 was associated with increased recurrence-free survival (HR = 1.138, 95%-CI:1.015-1.276, p = .027); the hazard for the primary outcome decreased by 12.1% per 1 mmHg decrease in mean EtCO2. 1-year and 5-year survival was also higher in the low-EtCO2 group. We did not find differences in the other secondary endpoints. - Conclusions - Lower intraoperative EtCO2 target values in CRC surgery might benefit oncological outcome and should be evaluated in confirmative studies.